2008
DOI: 10.1111/j.1399-3054.2008.01140.x
|View full text |Cite
|
Sign up to set email alerts
|

Physiological and cytological mechanisms of silicon‐induced resistance in rice against blast disease

Abstract: Rice (Oryza sativa L.) blast disease caused by Magnaporthe grisea is one of the most destructive diseases in the rice-growing areas of the world. Silicon is an important nutritional element especially for rice. Two near-isogenic lines of rice with different resistance to blast disease, i.e. CO39 (susceptible) and C101LAC (Pi-1) (resistant), were selected to determine the effects of Si amendment on the severity and incidence of rice blast disease. The physiological and cytological mechanisms involved in the ind… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

14
170
1
11

Year Published

2012
2012
2023
2023

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 261 publications
(196 citation statements)
references
References 37 publications
14
170
1
11
Order By: Relevance
“…The results of this study showed that application of silica gel and sodium silicate effectively reduced the severity and incidence of rice leaf blast. These results further confirm previous reports (Cai et al, 2008;Datnoff et al, 1997;Rodrigues and Datnoff, 2005). The results also revealed that plants treated with silica gel suffered lower levels of disease severity as compared with those treated with sodium silicate.…”
Section: Discussionsupporting
confidence: 82%
See 2 more Smart Citations
“…The results of this study showed that application of silica gel and sodium silicate effectively reduced the severity and incidence of rice leaf blast. These results further confirm previous reports (Cai et al, 2008;Datnoff et al, 1997;Rodrigues and Datnoff, 2005). The results also revealed that plants treated with silica gel suffered lower levels of disease severity as compared with those treated with sodium silicate.…”
Section: Discussionsupporting
confidence: 82%
“…The results also revealed that plants treated with silica gel suffered lower levels of disease severity as compared with those treated with sodium silicate. The mechanism of enhanced resistance to disease via Si application can be associated with accumulation of silicon in leaf epidermal cells which acts as a mechanical barrier against fungal infestation (Bowen et al, 1992;Cai et al, 2008). Seebold et al (2001) Showed that Si can alleviate disease severity through blocking of fungus ingress.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Higher accumulation of fungitoxic phenolic compounds due to silicon treatment protected Arabidopsis from powdery mildew caused by Erysiphe cichoracearum (Ghanmi et al, 2004;Fauteux et al, 2005). Increased activity of antimicrobial glycosylated phenolics, diterpenoid phytoalexins, and lignin decreased severity of blast disease in silicon-treated rice plants (Cai et al, 2008). Dallagnol et al (2011) found that decreased level of rice brown spot (Bipolaris oryzae) was due to enhanced accumulation of lignin and soluble phenolics.…”
Section: Antifungal Compoundsmentioning
confidence: 99%
“…Enhanced peroxidase activity in wheat leaves, due to silicon treatment, decreased the severity of powdery mildew caused by Blumeria graminis f.sp.tritici (Yang et al, 2003). Regarding the rice-M. oryzae interaction, increased resistance against the blast pathogen is characterized by higher accumulation of glucanase, peroxidase, polyphenol oxidase and phenylalanine ammonia-lyase (Rodrigues et al, 2003(Rodrigues et al, , 2004(Rodrigues et al, , 2005Cai et al, 2008). Liang et al (2005) found that enhanced peroxidases, polyphenoloxidases and chitinases activities due to silicon root application were eff ective in reducing powdery mildew severity in cucumber.…”
Section: Defense-related Enzymesmentioning
confidence: 99%